The prevalence of anti HBs among healthy reproductive-age female in Indonesia : National Health Survey 2007 - Vivi Setiawaty (Berita Kedokteran Masyarakat (BKM), 2018)
Introduction:Hepatitis B virus  during  pregnancy  has  a  high vertical  transmission  rate,  causing  fetal  and  neonatal hepatitis  and  maternal  mortality.  Neonatal hepatitis  can lead  to chronic  virus  carriage,  which in turn  may  lead  to  liver  cirrhosis  and  hepatocellular carcinoma in young adults. Acute Hepatitis B carries a particular risk, not only for the mother, but also for the newborn. Therefore identifying female in reproductive-age for anti HBs is a useful indicator for the immunity of the disease. Objectives: The aim of this study is was to determine the prevalence of anti HBs in healthy reproductive-age female during the national health survey in 2007. Methods:The data used was secondary data obtain from National Health Survey in healthy respondent in Indonesia in 2007. In this study, we analysed biomedical data that can be linked to the demographic data from public health questionaire. The samples were reproductive-age female aged 15 to 49 years. The Enzyme Linked Immunosorbent Assay (ELISA) kit (Murrex-Abbot Laboratories) was used for serodetection of anti HBs according to manufacturer instruction.  The number of respondents of reproductive-age female who were sampled in this analysis were 1302 respondents Results:The samples collections were obtained from urban area in 272 districts/municipalities in 33 provinces. The survey collected 7520 sera from all respondents. The 1302 of 7520 sera tested for anti HBs were reproductive-age female. Most of respondents were at 25 to 34 age group (481/1302,39.4%). Among 1302 sera, we found that 330 (25.4%) had positive anti HBs. A 117 of 1302 (8.9%) samples were pregnant women. A 32 of 117 (27.4%) pregnant women had positive anti HBs. A 81 of 1302 (6.2%) samples were delivered women. A 18 of 81 (22.2%) delivered-women had positive anti HBs.  Conclusions:The high seroprevalence of anti HBs among healthy reproductive-age females are a public health concern. Further comprehensive studies are required to provide epidemiological information for public health awareness in the community